SERPING1 Variants and C1-INH Biological Function: A Close Relationship With C1-INH-HAE - Drouet, Christian; López-Lera, Alberto; Ghannam, Arije; López-Trascasa, Margarita; Cichon, Sven; Ponard, Denise; Parsopoulou, Faidra; Grombirikova, Hana; Freiberger, Tomáš; Rijavec, Matija; Veronez, Camila L.; Pesquero, João Bosco; et al. (Frontiers in Allergy, 2022)
Hereditary angioedema with C1 Inhibitor deficiency (C1-INH-HAE) is caused by a constellation of variants of the SERPING1 gene (n = 809; 1,494 pedigrees), accounting for 86.8% of HAE families, showing a pronounced mutagenic liability of SERPING1 and pertaining to 5.6% de novo variants. C1-INH is the major control serpin of the kallikrein–kinin system (KKS). In addition, C1-INH controls complement C1 and plasminogen activation, both systems contributing to inflammation. Recognizing the failed control of C1s protease or KKS provides the diagnosis of C1-INH-HAE. SERPING1 variants usually behave in an autosomal-dominant character with an incomplete penetrance and a low prevalence. A great majority of variants (809/893; 90.5%) that were introduced into online database have been considered as pathogenic/likely pathogenic. Haploinsufficiency is a common feature in C1-INH-HAE where a dominant-negative variant product impacts the wild-type allele and renders it inactive. Small (36.2%) and large (8.3%) deletions/duplications are common, with exon 4 as the most affected one. Point substitutions with missense variants (32.2%) are of interest for the serpin structure–function relationship. Canonical splice sites can be affected by variants within introns and exons also (14.3%). For noncanonical sequences, exon skipping has been confirmed by splicing analyses of patients' blood-derived RNAs (n = 25). Exonic variants (n = 6) can affect exon splicing. Rare deep-intron variants (n = 6), putatively acting as pseudo-exon activating mutations, have been characterized as pathogenic. Some variants have been characterized as benign/likely benign/of uncertain significance (n = 74). This category includes some homozygous (n = 10) or compound heterozygous variants (n = 11). They are presenting with minor allele frequency (MAF) below 0.00002 (i.e., lower than C1-INH-HAE frequency), and may be quantitatively unable to cause haploinsufficiency. Rare benign variants could contribute as disease modifiers. Gonadal mosaicism in C1-INH-HAE is rare and must be distinguished from a de novo variant. Situations with paternal or maternal disomy have been recorded (n = 3). Genotypes must be interpreted with biological investigation fitting with C1-INH expression and typing. Any SERPING1 variant reminiscent of the dysfunctional phenotype of serpin with multimerization or latency should be identified as serpinopathy.